Faktor-faktor yang mempengaruhi kualitas perkawinan pada keluarga suami istri bekerja di Kota Bogor - Santy Fiscarini; Tin Herawati; Ujang Sumarwan (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
The quality of marriage reflects the harmonious relationship between husband and wife which is a factor in preventing divorce. The aim of this research is to analyze the factors that influence the quality of marriage in working husband and wife families. The research design is a cross sectional study. The research location is Bogor City, West Java. Research locations in government agencies and regionally owned enterprises (BUMD). The population of this study was husbands in husband-and-wife families working in government agencies and BUMDs in Bogor City. The number of respondents was 200 husbands (60 husbands worked as civil servants and 60 husbands worked as BUMD employees). Data was obtained by direct interviews using a structured questionnaire. Data were processed and analyzed using SPSS for Windows and SEM-PLS (Structural Equation Modeling - Partial Least Square). The research results show that the quality of marriage in working husband and wife families is influenced by husband-and-wife interactions. The SEM test results also show that there is an influence between other variables in this study. Gender relations have a positive effect on fathers' parenting styles and husband and wife interactions. Husband and wife interactions have a positive effect on fathers' parenting styles. The implication of this research is the importance of husband-and-wife interaction to improve the quality of marriage in working husband and wife families.